Lymphangioma of the ovary: etiology and management. (August 2016) - Radhouane, Achour; Mayada, Saadaoui; Khaled, Neji
Abstract: Lymphangioma of the ovary is an extremely rare lesion. It was first described in 1908[1] and there is only 19 cases reports in a 50-year literature survey[2] . Lymphangiomas are benign congenital malformations of lymphatic system. They are thought to happen due to obstruction of local lymph flow system and they can occur anywhere in the skin and the mucous membranes. Most common sites are the head and the neck and sometimes they can be found in the intestines, the pancreas and the mesentery. Lymphangioma of the ovary is a very rare tumor. Typically, lymphangiomas are slow-growing tumors that remain asymptomatic for a long time, with the tumor being identified incidentally during histopathological examination after excision. A 36-year-old women who consulted our department for infertility for 2 years. The systematic ultrasound examination reveals a right ovarian mass. The histologic analysis confirmed the diagnosis of cystic lymphangioma of the right ovary. She was planned for total laparoscopic tumorectomy with removal of all ovarian mass. The evolution was good for one year within Clinical and ultrasound monitoring. We report through this case report a review of the literature.